2017
DOI: 10.7150/jca.18055
|View full text |Cite
|
Sign up to set email alerts
|

Association between SNPs in Long Non-coding RNAs and the Risk of Female Breast Cancer in a Chinese Population

Abstract: Long non-coding RNAs (LncRNAs) have been reported to be involved in tumorigenesis and tumor progression. Single nucleotide polymorphisms (SNPs) in the lncRNAs also play a vital role in carcinogenesis. The aim of this study was to assess the relationships between the four selected tagSNPs (rs944289, rs3787016, rs1456315, rs7463708) in the lncRNAs and the risk of female breast cancer in a Chinese population. A case-control study was carried out involving in a total of 439 breast cancer patients and 439 age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Interestingly, Kang et al [ 10 ] and Xu et al [ 11 ] also revealed a significant association between rs3787016 with risk of esophageal cancer and breast cancer, which highlighted that POLR2E rs3787016 polymorphism might servers as a common genetic factor to affect individual susceptibility to cancer. To address this issue, for the first time, we here evaluated the association between rs3787016 and risk of liver and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kang et al [ 10 ] and Xu et al [ 11 ] also revealed a significant association between rs3787016 with risk of esophageal cancer and breast cancer, which highlighted that POLR2E rs3787016 polymorphism might servers as a common genetic factor to affect individual susceptibility to cancer. To address this issue, for the first time, we here evaluated the association between rs3787016 and risk of liver and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of this relationship have been revealed in multiple disease processes, including carcinogenesis ( 40 ). For example, a study found that the TT genotype of rs3787016 was related to the risk of breast cancer and the clinicopathological features of the tumour among premenopausal women ( 41 ). To integrate the SNP information with the NONCODEv5 human transcripts, we collected lncRNA–SNP associations from LincSNP 2.0 ( 35 ).…”
Section: Statistical Analysis Of Noncodementioning
confidence: 99%
“…Moreover, the dysregulation of a number of lncRNA targets, has correlated with the prognosis and diagnosis of a plenty number of cancer types including prostate cancer (141,142), lung cancer (143), and breast cancer (144)(145)(146), among other tumor types (147,148), as well as being linked to detention against chemotherapy and targeted therapy (149)(150)(151)(152). Correlation with a great number of analyses, indicates that these molecules are upregulated in cancer cells that are resistant to DNA damage inducers (153)(154)(155)(156), targeted therapies or antihormone therapies (141,(157)(158)(159).…”
Section: Lncrnas and Human Malignanciesmentioning
confidence: 99%